ANALISIS INDUSTRI GARAM LOKAL DI KABUPATEN REMBANG (PENDEKATAN STRUCTURE-CONDUCT-PERFORMANCE) - Huda, Nailul; Sugiyanto, FX (Diponegoro Journal of Economics, 2013)
Salt is a vital commodity for the country's economy. Indonesia is a maritime country with a long coastline. Indonesia should be able to produce his own salt to meet the needs of the national salt. However, Indonesia would import salt in order to meet national needs. With the abundance of salt available in the market, the price of salt to be dropped. Government policy gives farmers a price limit. However, in practice the price of salt peasants selling far below the selling price set by the government. This is due to an unbalanced market power in the distribution chain between farmers and traders salt collectors. This study aims to identify and analyze the market structure of salt farmer and salt middletrader (tengkulak), analyze the role of salt farmer and salt middletrader in the market, analyze vertical integration of middletrader to farmer, and analyze the effect of market share, productivity, and capital to labor ratio (CLR)toward Â the share farmer margins.This analysis uses descriptive qualitative and quantitative analysis approach to structure-conduct-performance (SCP). This study uses a simple regression model (OLS) to analyze the correlation between independent and dependent variables.The results of this study indicate the level of farmers' competitive market structure is monopolistic competition market structure and from the perspective of middletrader it is Â competition level is oligopsonistic. Middletrader have a important role in determining the agreed price because it has a better bargaining position than the farmers. The degree of vertical integration of middletrader to farmer is 1.05, which means that farmers do not have the power to influence the price.All independent variables have positive and significant impact on the dependent veriabel. Market share has a coefficient of 0.541 and 0.000 probability. Productivity variable has a coefficient of 1.319 and 0.000 probability. CLR variable has a coefficient of 0.778 and 0.026 probability.